2013
DOI: 10.1111/trf.12165
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced detection of hepatitis B virus in Hong Kong blood donors after introduction of a more sensitive transcription‐mediated amplification assay

Abstract: The observed greater than twofold enhanced WP NAT yield with the Ultrio Plus assay can be explained by greater than 10-fold increased analytical sensitivity in detecting the HBV Genotype B and C strains in Hong Kong. Direct comparison studies of the two assay versions on dilutions of HBV NAT-yield samples are required to confirm this hypothesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
79
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(84 citation statements)
references
References 30 publications
4
79
1
Order By: Relevance
“…However, in the light of the results obtained in this study, these recommendations should be revised in order to either exclude all anti-HBc-positive donors or to rescind the current NAT strategy and replace it with the most sensitive NAT applied to individual donation samples [9]. Notably, the prevalence of antiHBc antibodies among candidate donors is expected to decrease in the future as a result of vaccination and declining incidence of new infections.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, in the light of the results obtained in this study, these recommendations should be revised in order to either exclude all anti-HBc-positive donors or to rescind the current NAT strategy and replace it with the most sensitive NAT applied to individual donation samples [9]. Notably, the prevalence of antiHBc antibodies among candidate donors is expected to decrease in the future as a result of vaccination and declining incidence of new infections.…”
Section: Discussionmentioning
confidence: 91%
“…However, HBV transfusion-transmission cannot be completely excluded since the pooling procedure reduces the assay's analytical sensitivity [9], and in fact a recent report indicated that the likelihood of detecting OBI donations by NAT increased when the size of the pool was decreased from 50 to 20 donations or when the test sensitivity was increased by a small margin [9][10][11]. As recently pointed out [5], studies on the safety of the current screening policies would require the testing of matched recipient specimens collected before and after transfusion.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the prevalence of OBI in Taiwan was 0.1% (from 10727 seronegative blood donors) (12), whereas in Hong Kong this was reported as 0.13% (4/3044) and 0.11% (11/9967) for two cohorts (13). However, in other studies, after introduction of a more sensitive transcription-mediated amplification assay, the HBV NAT-yield rates of OBI were 1:5120 and 1:2450 by ID-NAT using Ultrio and Ultrio Plus assays (Novartis Diagnostics), respectively (P < 0.0001) (14). …”
Section: Discussionmentioning
confidence: 96%
“…The dramatic increase in the proportion of reactive results in this subset of HBsAg‐yield samples indicates that there may be a subpopulation of HBV strains in South African donors that is poorly detected by the Ultrio assay and will be picked up with more than 10‐fold higher sensitivity by the addition of the TER in the Ultrio Plus assay. A similar hypothesis was formulated by Tsoi and coworkekrs who used mathematical modeling to explain a more than twofold higher WP NAT yield in Hong Kong blood donors after the Ultrio assay was replaced by the Ultrio Plus assay. Since similar results were found by us in South Africa our earlier reported residual risk estimates based on 95 and 50% LODs of the Ultrio assay on the Eurohep HBV Genotype A2 standard need to be reassessed.…”
Section: Discussionmentioning
confidence: 99%